Practical approaches to network technology education: a study within secondary institutions in Kazakhstan - Zulpykhar, Zhandos; Serikbayeva, Aiym; Spirina, Yelena; Janabayev, Dauren; Sirojiddinova, Iroda (Frontiers in Education, 2025)
The experimental study examines instructional strategies for teaching network technologies in secondary education, specifically within Kazakhstan's Nazarbayev Intellectual School (NIS) curriculum. Through pre-test and post-test assessments, the study explores the impact of hands-on, practical learning activities on students' comprehension and understanding of network education. Findings indicate that interactive learning methods significantly enhance students' retention and application of network technology concepts. This study suggests that hands-on approaches are instrumental in improving technical understanding in similar educational contexts.